E-SIABA SEBAGAI MEDIA EDUKASI DIGITAL DALAM PENINGKATAN PENGETAHUAN ORANG TUA TENTANG DEMAM ANAK - Zelly Hofalia, Lingga; Munir, Zainal; Eka Candra Dewi, Novela (Jurnal Keperawatan dan Kesehatan, 2026)
Background: Fever is one of the most common health problems in children and often causes anxiety among parents. Inappropriate handling due to limited knowledge can worsen the child's condition. Objective: This study aimed to determine the effect of electronic education based on chayote and shallots (E-SiaBa) on parental knowledge in managing fever in children. Methods: The research used a pre-experimental design with a one-group pretest-posttest approach. A total of 75 parents with toddlers at Posyandu Mawar, Wringin Village, were involved as respondents. The intervention was delivered through an audio-visual educational video for one week. Data were collected using questionnaires and analyzed using the Wilcoxon test. Results: The results showed a significant increase in parental knowledge after the intervention (p = 0.000). Conclusion: In conclusion, E-SiaBa is effective in improving parental knowledge in managing childhood fever. This media can be an alternative educational tool that is practical, accessible, and based on local wisdom.